Desiring Whiteness in Jasmine - Shrestha, Ravi Kumar (Patan Prospective Journal, 2022)
The novel Jasmine is written by Bharati Mukherjee, a South Asian English novelist. The novel revolves round Jasmine, the protagonist, who migrates to America desiring whiteness. My major argument in the research article is that she is obsessed with whiteness to have American identity, to materialize her husband’s dream of migrating to the USA, to counter the cultural binding of widowhood prevalent back in her home land, India and to have the privilege of gender equality by shifting to America. The study reflects how on the one hand, Jasmine’s journey to America is influenced by transnationalism and globalization; on the other hand, whiteness primarily appears to her as her desire and it also appears to her as identity, threat and negotiation. For the broad theoretical framework, I have used Kalpana Seshadri- Crooks’ and Frantz Fanon’s theory as theoretical modality to deal with the theory of whiteness. The novel reveals Jasmine, a young Indian girl’s journey from her village Hasnapur in India to Iowa in the USA, the land dominated by whites. Her migration to the USA, the assumed land of gender equality and opportunity shows her obsession with whiteness. Her movement from illegal migration to being an immigrant in pursuit of an American identity uncovers her belief of transcending the cultural barriers and taboos of home land. KalpanaSeshadri-Crooks defines whiteness as “a master signifier that establishes a structure of relations, a signifying chain that through a process of inclusions and exclusions constitutes a pattern for organizing human difference” (3). Likewise, Samir Amin argues “Whiteness is entirely related to Europe or the eternal west” (89), which can be a relevant idea to support why Jasmine migrates to the USA. Besides, the non-whites travel from the colonized nations to the west in search of whiteness, while whiteness travels from the west to the east to assert the hegemony over the orients. In this light, France Widdance Twine and Charles Andrew Gallagher further urge “Whiteness as a form of privilege and power travels from western countries to colonies throughout the world” (10). Finally, the write-up focuses on the significance of the study of desiring whiteness of South Asian characters like Jasmine for their migration to the USA.